Women Workers, Labor Protection, and Informal Employment in Indonesia’s Digital Economy - Florentinus Michael Adam (JUSTISIA GLOBAL EDUKASI, 2026)
The rapid expansion of Indonesia’s digital economy has generated new employment opportunities while simultaneously creating challenges for labor protection, particularly for women workers engaged in informal and platform-based work. This article investigates the intersection of gender, labor rights, and digital employment by examining the legal protection available to women workers in Indonesia’s evolving digital economy. Using a socio-legal research approach, the study analyzes labor regulations, policy frameworks, and existing literature on digital labor markets. The findings demonstrate that women increasingly participate in gig work, online commerce, and platform-mediated services due to the flexibility these arrangements provide. However, such forms of employment often fall outside traditional labor protections, exposing women to income insecurity, discrimination, lack of social security coverage, and heightened vulnerability to exploitation. The study also reveals that existing labor regulations struggle to address the ambiguous legal status of platform workers, creating regulatory gaps that disproportionately affect women. From a feminist legal perspective, the article argues that labor policies must recognize gender-specific vulnerabilities and address structural inequalities embedded within digital labor markets. Effective labor protection requires a combination of regulatory reform, expanded social protection mechanisms, and gender-responsive employment policies. This research contributes to emerging scholarship on digital labor governance and highlights the need for inclusive legal frameworks capable of balancing innovation, economic growth, and workers’ rights. The findings offer practical recommendations for policymakers seeking to promote decent work and gender equality in Indonesia’s digital transformation.